Intensification of Kalimantan White Pepper (Piper nigrum) Oil Extraction Based on Microwaves and Ultrasonics - Gotama, Bangkit; Addina, Khalisa; Ananda, Nur Afrie Rizqie (Jurnal Online Pertanian Tropik, 2022)
White pepper is one of the staple spices of East Kalimantan. In order to boost the competitiveness of white pepper commodities, it is necessary to raise the added value of the commodity by transforming it into high-value goods, such as white pepper oil. This research intends to evaluate the production of local (LPL) white pepper oil (MLP) with commercial white pepper oil (LPK) using different extraction techniques (microwave-assisted hydro distillation, MAHD; and ultrasonic following hydro distillation, US-HD). This experiment also evaluated the effect of extraction factors on oil yield, including microwave power on MAHD, ultrasonic wave power on US-HD, sonication duration on US-HD, and solvent volume. A comparison of the energy usage of both approaches was also conducted in order to identify the most effective approach. The MAHD and US-HD techniques were used to extract 80 grams of dry white pepper powder mixed with aquadest for 90 and 180 minutes, respectively. Specifically for US-HD, the combination of raw materials was sonicated for 3-5 minutes prior to extraction utilizing the HD method. In both MAHD and US-HD, LPK includes more MLP than LPL, according to experimental findings. MLP yield may be increased by the addition of solvent, wave power (micro and ultrasonic), and sonication time. Based on its efficiency and energy consumption, the US-HD approach is superior to the MAHD.